Women's financial capability and financial wellbeing : a study on community based organisations for sustainable development - Parvathy, V. K.; Kumar, Jyothi (Routledge, 2025)
This book investigates the impact of financial capability and decision-making ability on the financial wellbeing of women associated with community based organisations (CBOs). In light of the evolving socio-economic landscape in South Asia and the growing gender disparity in poverty, there is an urgent need to address these issues at the grassroots level to achieve sustainable development. CBOs play a crucial role by providing a platform for women to discuss shared challenges, develop potential solutions and create livelihood opportunities.Drawing on data from Asia's largest women's community network, this book examines how Kudumbashree, as a successful model, can serve as a guiding framework for other community networks across South Asia. It also investigates how demographic factors such as age, marital status, education, income and family size influence women's financial capability. Furthermore, this book delves into the financial wellbeing of women and explores how addressing their needs can contribute to the attainment of the Sustainable Development Goals (SDGs).By examining global initiatives aimed at empowering women economically, this book offers valuable insights for policymakers, financial social workers, scholars and organisations dedicated to advancing financial wellbeing for women and promoting sustainable development.
Includes index.
Keywords: Women -- South Asia -- Finance, Personal.; Community development personnel -- South Asia -- Finance, Personal.; Community organization -- Economic aspects -- South Asia.; Women in sustainable development -- Economic aspects -- South Asia.; elektronické knihy; electronic books